P131 A NEW THREE-STEP HYBRID APPROACH IS A SAFE PROCEDURE FOR INCISIONAL HERNIA: EARLY EXPERIENCES WITH A SINGLE CENTRE RETROSPECTIVE COHORT. (25th November 2021) - Van den Dop, Matthijs; Smet, Gijs De; Bus, Michaël; Lange, Johan; Koch, Sascha; Hueting, Willem
Abstract: Aim: In this study, a three-step novel surgical technique was developed for incisional hernia, in which a laparoscopic procedure with a mini-laparotomy is combined: so-called 'three-step incisional hybrid repair'. The aim of this study was to reduce the risk of intestinal lacerations during adhesiolysis and recurrence rate by better symmetrical overlap placement of the mesh. Material and Methods: From 2016 to 2020, 70 patients (65.7% females) with an incisional hernia of > 2 and ≤10 cm underwent an elective three-step incisional hybrid repair in two non-academic hospitals performed by two surgeons specialised in abdominal wall surgery. Intra- and postoperative complications, operation time, hospitalisation time and hernia recurrence were assessed. Results: Mean operation time was 100 min. Mean hernia size was 4.8 cm; 45 patients (64.3%) had a hernia of 1–5 cm, 25 patients (35.7%) of 6–10 cm. Eight patients had a grade 1 complication (11.4%), five patients a grade 2 (7.1%), two patients (2.8%) a grade 4 complication and one patient (1.4%) a grade 5 complication. Five patients had an intraoperative complication (7.0%), two enterotomies, one serosa injury, one omentum bleeding and one laceration of an epigastric vessel. Mean length of stay was 3.3 days. Four patients (5.6%) developed a hernia recurrence during a mean follow-up of 19.5 weeks. Conclusions: A three-step hybrid incisional hernia repair is a safe alternative for incisional hernia repair. Intraoperative complications rate was low.